(untitled) (Estudios Sociales, 2019)
In the light of «society» as a historical construction, the article aims at reconstructing the process of introducing the concept of social cohesion in Argentina and some of the ways it was absorbed and used throughout the nineteenth century. It argues that sociology emerged in the region at the end of the 19th century as a science seeking to offer analytical and methodological tools needed to give a scientific response to the problem of social cohesion. It gives an account of the modalities of diffusion of this new way of thinking the concept of social, which exceeds both the academic boundaries and the political potentialities of these new analytical tools. The article focuses on the introduction of objective sociology within a Durkhemian orientation at the University of Buenos Aires. To that end, it isolates this historical moment from the teleological device, which describes it as a «failure», and regards it as a «scope of possibilities». This new perspective has been possible as the introduction of the problem of social cohesion opened up throughout the twentieth century.